The impact of participatory action research and endogenous integrated soil fertility management on farm-gate dietary outputs in Northern Tanzania - Mponela, Powell; Manda, Julius; Kinyua, Michael Wanjohi; Maguta, Job Kihara (Elsevier, 2023)
In most developing countries, although agricultural extension and research devolved since 1980s to promote relevance, cost-effectiveness, ownership, and sustainability, participatory action research (PAR) have been run, albeit with limited empirical evidence on their impacts on farmers livelihoods. The study use a three-stage extended regression model (ERM) to estimate the effect PAR and the promoted agronomic practices on crop produce dietary outputs considering potential endogenous engagement, omitted variable bias, reverse causality, endogenous covariates, and factor simultaneity. Using a sample of 607 small family farms with varying levels of research engagement in the Northern Highlands of Tanzania, the study found that PAR was associated with increased farm-gate dietary outcomes: per-capita calories, proteins, and minerals produced by 139, 216, and 143 %, respectively, and consumption of farm-produced minerals by 74–200 %. The organic manure application was associated with increased the dietary outputs by 62–113 % while the application of inorganic fertilizer with increased protein and mineral outputs by 68 and 105 %, respectively. The crop diversification was associated with increased dietary outputs by 11–25 % while pest and diseases control with increased dietary outputs by 12–17 % but with reduced consumption by 13–14 %. Soil and water conservation measures including terracing were associated with decreased dietary outputs. These findings indicate that PAR contributes to nutritional outcomes of smallholder farmers contingent on the promotion of low-cost input sources and crop diversification which can be leveraged to inform upscaling of participatory policies, strategies, and technologies.